Local buckling of 800 MPa high strength steel welded T-section columns under axial compression. (1st September 2019) - Cao, Xianlei; Gu, Lixiang; Kong, Zhengyi; Zhao, Geng; Wang, Min; Kim, Seung-Eock; Jia, Dongyun; Ma, Cuiling
Highlights: Embedding coefficients for flange and web were suggested. Different width-thickness ratio limits for flange and web were suggested. A new model was proposed for estimating the ultimate load of columns. Abstract: Local buckling behavior of welded T-section column, which was fabricated from 800 MPa high strength steel (HSS), was investigated in this study. An experimental study consisting of eleven welded T-section columns under axial compression was carried out. The failure mode characterized by local buckling of plates was found, and different load-displacement curves of specimens were established. Embedding coefficients including the effect of flange on the web buckling and the effect of web on the flange buckling were suggested. A finite element (FE) model for predicting the ultimate load of specimens was developed, which was then verified by test data. Comparison of width-thickness ratio limits for flange and web between various specifications and test data were made. Chinese Specification GB50017-2017 overestimated the ultimate load, and American Specification ANSI/AISC 360-10 was a little underestimated. A new model modified from Chinese Specification GB50017-2017 was proposed for estimating the ultimate load of 800 MPa high strength steel welded T-section columns under axial compression, and a good agreement between the proposed model and test data was made.